THE STUDENTS’ PERCEPTION OF THE EFFECTIVENESS OF ENGLISH AND ARABIC TEACHING AND LEARNING AT THE LANGUAGE AND CULTURE CENTER OF STATE INSTITUTE FOR ISLAMIC STUDIES SHEKH NURJATI CIREBON - Mahmud, Mahmud; Wiedarti, Pangesti (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2014)
This study aimed to explore the effectiveness of English and Arabic teaching and learning the Language and Culture Center (LCC) at the State Institute for Islamic Studies Shekh Nurjati Cirebon (SIIS SNJ) based on the students’ perception. The study is to find out students’ opinion toward English and Arabic teaching and learning process and provide beneficial information for the teaching system in the LCC. This study used descriptive survey approach. The subjects were the students of English and Arabic intensive program. The data were collected through the questionnaire The results of the study are as follows. First, the teaching quality indicator is categorized as fairly effective. Second, the generic skills indicator is categorized as less effective. Third, students’ motivation indica-tor is categorized as less effective. Fourth, learning resources is categorized as not effective. Fifth, the assessment appropriateness is categorized as fairly effective. Sixth, the students’ workload is catego-rized as less effective. Seventh, the curriculum content is categorized as less effective. Keywords: students’ perception, teaching and learning, effectiveness.